Utility of Reticulocyte Hemoglobin Equivalent in Screening for Iron Deficiency in Pregnancy - Haizler-Cohen, Lylach; Saeed, Haleema; Quiett, Valencia; Kaur, Gurpinder; Tefera, Eshetu A.; Gizaw, Samrawit; Verstraete, Richard; Auerbach, Michael; Hazen, Nicholas (American Journal of Perinatology, 2024)
Ferritin, commonly used for diagnosing iron deficiency (ID) in pregnancy, is limited by high cost and false elevations during inflammation. Reticulocyte hemoglobin equivalent (Ret-He), an alternative marker for ID, is unaffected by inflammation and analyzed on the same collection tube as the standard complete blood count (CBC). We aimed to determine the accuracy of Ret-He in detecting ID in pregnancy compared to ferritin in a U.S. cohort.This prospective cohort study enrolled 200 pregnant participants, recruited in any trimester if a CBC was drawn as part of routine prenatal care. For those who agreed to participate, Ret-He and ferritin were collected concurrently with the CBC. ID was defined as ferritin level below 30 ng/mL. Patients were classified into three groups based on hemoglobin and ferritin results to determine the severity of ID: no ID, ID alone, and ID anemia (IDA). Four participants with anemia but normal ferritin were excluded. Receiver operating curve analysis, including the area under the curve (AUC), was performed to assess the accuracy of Ret-He in detecting ID. A one-way ANOVA (analysis of variance) with post-hoc analysis was used to compare differences in Ret-He between the three groups of ID severity.The prevalence of ID in our cohort was 82% (161/196). The AUC for Ret-He was 0.65 (95% confidence interval: 0.55–0.75), indicating suboptimal discrimination between patients with and without ID. Ret-He was significantly different among the three groups (p < 0.001). In post-hoc analysis, Ret-He was significantly lower in the IDA group compared to the ID group (p < 0.001) but there was only a trend of lower Ret-He in the ID group compared to the non-ID group (p = 0.38).Ret-He has low accuracy in diagnosing ID in pregnancy. It may be useful in detecting severe ID resulting in anemia but not a mild iron-deficient state resulting in ID only.
Keywords: anemia; ferritin; iron deficiency; pregnancy; reticulocyte; reticulocyte hemoglobin equivalent